Innovating with potassium-modified ceramic powder geopolymer mortar and the integration of recycled aggregates - Kotanci, Ilyas; Uysal, Mucteba; Balaban, Mazem; Bendjilali, Fatiha; Aygun, Beyza Fahriye (ELSEVIER, 2024)
This study develops an environmentally friendly geopolymer mortar (GM) that incorporates ceramic powder (CP) and recycled aggregate (RA), optimized through the use of potassium hydroxide (KH) and potassium silicate (KS) as alkaline activators under varied molarities and curing conditions. The research methodically evaluates the replacement of ground granulated blast furnace slag (GBFS) with CP at different ratios (25 %, 50 %, 75 %, and 100 %). Subsequently, RA is replaced with marble powder (MP) and glass powder (GP) in proportions of 25 %, 50 %, and 75 %. Physical and mechanical properties, including unit weight, water absorption, ultrasonic pulse velocity (UPV), compressive strength and flexural strength, are evaluated at various curing times. Furthermore, exposure to elevated temperatures and freezing-thawing cycles test the material's durability. Specifically, a peak improvement of 45.4 % in compressive strength is observed with 50 % GP replacement of 100 % RA, while high temperature resistance tests show increases of 28.57 % in compressive strength and 26.75 % in flexural strength at 800 degrees C. The incorporation of GP also has a minimal impact on freezing-thawing resistance, with a slight reduction of 5.84 % in compressive strength and 5.78 % in flexural strength. Advanced microstructural analysis using scanning electron microscopy (SEM), X-ray diffraction (XRD), and Fourier Transform Infrared (FT-IR) spectroscopy reveals intricate details, confirming the significant efficacy of GP in improving GM properties. Furthermore, the analysis establishes a 94 % correlation between UPV and compressive strength and demonstrates the effectiveness of the material composition and processing conditions tailored to this study.
Keywords: Geopolymer mortar; Ceramic powder; Marble powder; Glass powder; Recycled aggregate; Potassium activators; Mechanical and durability properties; FLY-ASH GEOPOLYMER; PARTIAL REPLACEMENT; CONCRETE; WASTE; PERFORMANCE; BEHAVIOR; CEMENT; Construction & Building Technology; Engineering